IMPACT INVESTING VS. PHILANTHROPY: A COMPARATIVE ANALYSIS OF FUNDING MODELS FOR LONG-TERM SUSTAINABILITY IN SOCIAL ENTREPRENEURSHIP - Murah Murah; Rashid Rahman; Robert Harris (Journal of Social Entrepreneurship and Creative Technology, 2025)
Social entrepreneurship has emerged as a critical force for addressing complex global challenges. However, the long-term sustainability of these ventures remains a significant hurdle. A central debate within the sector concerns the efficacy of its two primary funding paradigms: traditional grant-based philanthropy, which prioritizes social outcomes, and market-driven impact investing, which demands both social and financial returns. This research provides a rigorous comparative analysis of impact investing and philanthropic funding models. It specifically investigates how each model distinctly influences the long-term operational and financial sustainability, scalability, and mission integrity of established social enterprises. A qualitative, multiple case study methodology was employed. The study analyzed a purposively selected sample of (n=12) mature social enterprises, stratified into two cohorts: six funded primarily by philanthropy and six funded primarily by impact capital. Data were gathered via semi-structured interviews with founders/CEOs and longitudinal analysis of organizational reports and financial statements. The findings indicate that philanthropic funding is essential for early-stage risk-taking and deep-impact programming but often correlates with restricted growth and long-term funding dependency. Conversely, impact investing successfully drives operational discipline and scalability. This model, however, introduces significant pressures that increase the risk of “mission drift” as enterprises prioritize financial benchmarks over core social objectives. Neither funding model is unilaterally superior. The research concludes that long-term sustainability in social entrepreneurship is not an “either/or” proposition. It is best achieved through a strategically phased, hybrid financial ecosystem that leverages philanthropy for mission-critical capacity-building and impact investing for scaling proven, market-based solutions.